The Effectiveness of Mobile Court Implementation in Manado Religious Court - Lahilote, Hasyim Sofyan (Institut Agama Islam Negeri Curup, 2022)
This article discusses the implementation of the mobile Court conducted by the Manado Religious Court. This research is qualitative field research using empirical legal methods. The aim is to determine the dominant factors that affect the effectiveness of the mobile court conducted by the Manado Religious Court. By using the Legal System theory proposed by Lawrence M. Friedman, the author tries to unravel the problems that often arise in the mobile court process. The results of the study indicate that there is a significant relationship between the knowledge and awareness of justice seekers who use the judiciary, especially the Religious Court. The success implementation of mobile courts is due to the coordination and readiness of judicial infrastructure, including efforts to socialize the practice of mobile courts to related agencies, which are enhanced to achieve the goals of implementation of the mobile court.